INNOVATIONS TO SUPPORT THE REHABILITATION PROCESS FOR PEOPLE WITH DISABILITIES - Gnatiuk, Liliia Romanivna; Zhuravlova, Kseniia Serhiivna (Theory and practice of design, 2023)
The rehabilitation of servicemen and women in Ukraine after warrelated injuries is extremely relevant and vital for the physical, psychological and social well-being of veterans and has significant implications for their successful reintegration into civilian life. This project presents the innovation means of rehabilitation for military personnel in Ukraine, focusing on institutions and their goals. Additionally, international assistance programs aimed at supporting Ukrainian soldiers in their rehabilitation are discussed. The research methodology includes a review of available literature, reports and official documents. The results of the study highlights the challenges and opportunities in providing rehabilitation services to military personnel in Ukraine, and have implications for project practice in the field of health care and support services. The purpose of the study is to reveal the accessibility, ergonomics and application of universal design in the equipment that fills rehabilitation centers in Ukraine. Additionally, the work aims to study, analyze and solve various aspects related to the infrastructure and equipment in these centers, as well as present a personal development. Given that the institutions are aimed at effectively meeting the needs of their diverse clientele, including military personnel and veterans. The study can also be useful for design practice in the field of health care and support services, as it takes into account the specific needs of veterans, including accessibility of facilities, mental health services, and vocational training programs. Methods. The research methodology included an analysis of the structure and functions of institutions, as well as an assessment of international assistance programs and experience available to Ukrainian soldiers [6]. Although the data of specific study participants are not provided for reasons of confidentiality in the context of war, the conclusions are based on publicly available information and expert analysis. To gather information, a comprehensive review of available literature, official reports and documents related to the rehabilitation of military personnel in Ukraine was conducted. Scientific novelty. Implementation of the technologies developed and considered during the research will improve the quality of medical care for servicemen and women and ensure equal access to safe, effective and inclusive rehabilitation services, facilities and conditions. Practical significance. Based on the conducted research, a personal innovation is presented to support the rehabilitation process of people with disabilities.